Challenges Facing Traditional Power Structures in Resolving Property Inheritance Conflicts in Meru County, Kenya - Gakii, Mbaabu Esther; Onkware, Kennedy; Were, Edmond (International Journal For Research In Educational Studies, 2018)
In Africa, traditional power structures are used alongside conventional justice system in many countries to resolve conflict related to property inheritance. These are the respective customary decision making organs in the society whose authority is believed to originate from the ancestors and was believed to be divine. Therefore, their decisions cannot be questioned or altered. The study assessed the challenges facing the traditional power structures in resolving property inheritance conflicts in Meru County, Kenya. This study employed a descriptive survey research design to gain insight into the challenges facing traditional power structures in resolving property inheritance conflicts in Meru County, Kenya. Qualitative and quantitative data was collected. The sample size included all the 54 Njuri Ncheke committee members consisting of the chairperson, the secretary and the treasurer from all the 18 Njuri Ncheke Centres in Tigania East, 180 elders and 42 heads of households whose inheritance conflict cases were resolved by Njuri Ncheke. Data was collected using in-depth and key informant interviews, Focus Group Discussions (FGDs), and direct observation. Data gathered from the study was coded and analyzed according to themes emerging from the narratives. The study revealed that the challenges facing Njuri Ncheke as an institution resolving inheritance related conflicts in Tigania East included, either of the parties being compromised, or of patriarchal cultural influence on the part of the council, other challenges included lack of awareness on changes in the law, and inadequate use of technology. The study recommended public education to the residents about what Njuri Ncheke as a traditional institution stands for and why it is structured as it is by including it in the education curriculum for all schools in the areas served by Njuri Ncheke. This will enhance understanding and appreciation of the functions of this traditional institution.